2019
DOI: 10.1111/bpa.12719
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological lesions in the very old: results from a large Brazilian autopsy study

Abstract: Objective To compare neuropathological correlates of cognitive impairment between very old and younger individuals from a Brazilian clinicopathological study. Methods We assessed the frequency of neuropathological lesions and their association with cognitive impairment (Clinical Dementia Rating scale ≥0.5) in the 80 or over age group compared to younger participants, using logistic regression models adjusted for sex, race and education. Results Except for infarcts and siderocalcinosis, all neuropathological le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
4
23
2
Order By: Relevance
“…The frequency of cerebrovascular changes was low in general in our cohort, similar to low rates of cerebrovascular changes in this age group found in other series. 14…”
Section: Participantsmentioning
confidence: 99%
“…The frequency of cerebrovascular changes was low in general in our cohort, similar to low rates of cerebrovascular changes in this age group found in other series. 14…”
Section: Participantsmentioning
confidence: 99%
“…
Thank you for the opportunity to respond to the letter of Drs. Dani and Pittella concerning our recently published article "Neuropathological lesions in the very old: results from a large Brazilian autopsy study" (5). In this work analyzing the distribution of common neuropathological lesions associated with cognitive decline in individuals who died between the 6th and 8th decade of life vs. older individuals, we found a higher frequency of neuropathological lesions in the very old group.
…”
mentioning
confidence: 56%
“…Dani Pittella understood that we suggested the differences in the distribution of the neuropathological lesions between age groups were related to ethnic factors. However, this was a misunderstanding as we never reported this possibility in our manuscript since the interaction term between race and the age groups was not significant (5). Besides, Drs.…”
Section: Dear Editormentioning
confidence: 76%
“…Similar results were observed by Osuntokun et al (4) in the analysis of betaamyloid deposition in the brains of non-demented Nigerian Africans. The conclusions by Suemoto et al (6) and Schlesinger et al (5) are unwarranted, since their patients are of admixed ethnicity and no valid genetic marker related to ethnicity has been studied by the authors. Our previous cytophotometric and morphometric work on the entorhinal cortex of 300 autopsied individuals without dementia across three distinct ethnic groups (Brazilian, Japanese and German patients aged 40-89 years) suggests that differences in the frequency of NP and NFT, as well as the rate of progression from NP to NFT-so called neurodegeneration progression rate-may vary remarkably, depending on neuronal size (1)(2)(3).…”
Section: Dear Editormentioning
confidence: 96%
“…Suemoto et al (6) reported differences in neuropathological lesions in the very old and younger individuals from a large Brazilian autopsy study as being possibly related to ethnic factors. In previous work, the same authors demonstrated that African ancestry was inversely correlated with neuritic plaques (NP), but not with neurofibrillary tangles (NFT), compared to Caucasian ancestry (5), also suggesting that unknown genetic variants or environmental factors associated with African ancestry reduce the accumulation of β-amyloid or increase its clearance.…”
Section: Dear Editormentioning
confidence: 99%